Istishna’ dalam Transaksi Sistem Cash on Delivery (COD) pada Jual Beli Online - Syahila Sukmana, Ahyana; Sabbar, Sabbar Dahham (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study analyzes the application of the istishna’ contract in the Cash on Delivery (COD) system for online transactions from an Islamic law perspective. Using a conceptual and normative approach, this research explores the compliance of COD transactions with the pillars and conditions of the istishna’ contract, as well as the challenges in its implementation. The findings indicate that although the COD system can fulfill the elements of the istishna’ contract, several potential issues arise, such as unilateral order cancellations by buyers, unclear product specifications, and payment uncertainties, which may lead to injustice for sellers and delivery service providers. Therefore, clearer regulations in Islamic e-commerce are necessary, including an escrow mechanism based on the wadi’ah contract to ensure transaction security. This study highlights the importance of a more adaptive istishna’ contract model in digital e-commerce, ensuring balanced protection for all parties in accordance with the principles of justice in Islamic economics.